Trypsin/α-Amylase Inhibitors from Capsicum chinense Seeds: Characterization and Antifungal Activity against Fungi of Agronomic Importance - da Silva, Marciele S.; de Azevedo dos Santos, Layrana; Taveira, Gabriel Bonan; Nagano, Celso Shiniti; Chaves, Renata Pinheiro; de Oliveira Carvalho; Rodrigues, Rosana; Gomes, Valdirene Moreira (Protein and Peptide Letters, 2023)
Background: Protease inhibitors (PIs) have attracted attention due to their important roles in plant defense. Objective: The objective of this work was to characterize and evaluate the antimicrobial activity of the peptides of a family of serine PIs from Capsicum chinense Jacq. seeds. Methods: Initially, PIs were extracted from the seeds and subjected to purification by chromatography, resulting in three different peptide enriched fractions (PEFs) termed PEF1, PEF2 and PEF3. Subsequently, the PEF3 was subjected to trypsin inhibition assays, α-amylase activity assays, antimicrobial activity assays on phytopathogenic fungi, and assays to determine the likely mechanisms of action. Results: The PEF3 was composed of three protein bands with molecular masses ranging between 6 and 14 kDa. The amino acid residues of the 6 kDa band showed high similarity with serine PIs. PEF3 inhibited the activity of the enzymes trypsin, human salivary α-amylase, and Tenebrio molitor larval α-amylase and inhibited the growth of phytopathogenic fungi, showing 83.7% loss of viability in Fusarium oxysporum. PEF3 induced reactive oxygen species in Colletotrichum lindemuthianum and F. oxysporum to dissipate their mitochondrial membrane potential and activated caspases in C. lindemuthianum. Conclusion: Our results reinforce the importance of PIs in plant defense mechanisms against phytopathogenic fungi as well as in their biotechnological applications for the control of plant pathogens.
Keywords: α-amylase inhibitor